Nursing intervention for quality of life in patients with ostomy: A systematic review - Abbas Heydari; Zahra Sadat Manzari; Zohre Pouresmail (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: Ostomy-related challenges in everyday life may negatively affect patients' Quality of Life (QL), even long after ostomy surgery. Nurses provide care interventions that may have a significant effect on the patients' QL. Therefore, the purpose of the present study was to determine evidence of effective nursing interventions on the QL of patients with an ostomy. Materials and Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. English articles published from 2000 to 2021 were identified and retrieved from PubMed, Medscape, MedlinePlus, ScienceDirect, Web of Science, Scopus, Wiley Online Library, ProQuest, ClinicalKey, SAGE, IRCT, and Cochrane. We assessed all included studies (18 articles) using the JBI Critical Appraisal Checklist. Results: Interventions reviewed in the study were categorized based on intervention, content of nursing intervention, training method, and target group of the nursing intervention. The nursing interventions involved natural treatments, self-care, and psychological support for patients. The training methods used in the studies included demonstration and lecture, mixed media presentation including PowerPoints, and Internet tools such as WeChat Applications. Some interventions were only presented to patients, caregivers, caregivers and patients together, or peer patients. Conclusions: According to the results of the present study, it is suggested that a regular care plan be used with the participation of families and patients from pre-operational to discharge along with nurses' follow-ups and home care to promote the QL. A combination of self-care and psychological education can promote these patients' QL.